Dead man's hand - Taylor, Brad, 1965- (Taylor, Brad, 1965- Pike Logan thriller, 2024)
To finally end the war between their nations, a rogue Ukrainian band of partisans known as the Wolves teams up with members of Russia's military intelligence to assassinate Vladimir Putin. But Putin is aware of the traitors in his midst and assigns the loyal commander of the Russian national guard to root them out. It's a mission Victor Petrov is expected to undertake after he prevents Sweden from joining NATO, by assassinating a deputy minister of foreign affairs. After receiving intelligence about the threat in Sweden, the U.S. sends Pike Logan to identify Victor's target, only for him to get caught in the crossfire between Putin's agents and the Wolves. When the smoke clears, Pike makes no effort to stop the Wolves on their ultimate mission, believing it just, until he discovers that their operation has unimaginable consequences. For Putin is preparing a devastating endgame: activating the Dead Man's Hand nuclear response that will launch Russia's missiles in the event of his death.